The Effects of Fire in Spruce Seedling Survival and Trophic Interactions in the Hudson Bay Lowlands of Churchill, Manitoba - Antoniadis, Melissa Kay (2015)
This study examined how post-fire changes in abiotic and biotic conditions affect the performance and survival of spruce seedlings, and the abundance and diversity of insect and microbe communities in the subarctic of Churchill, Manitoba. This thesis also explored how varying colour of pan traps attract distinct groups of insect species, as pan trap colours mimic flower colours. In general, increased levels of all of the abiotic factors were found to positively influence the performance of spruce seedlings, except for soil organic matter. It was also found that the forest which was once dominated by white spruce shifted post-fire to mainly shrub land likely as a result of changes in abiotic conditions and plant interactions. The abundance of both arthropods and microbes was significantly greater in unburned areas compared to burned sites. Microbe concentrations were higher when measured on the ground compared to vegetative leaf surfaces, and yellow pan traps had the greatest arthropod capture rates.